Specific Cross-reaction of IgG Anti-phospholipid Antibody with Platelet Glycoprotein IIIa - Tokita, Shigeru; Arai, Morio; Yamamoto, Naomasa; Katagiri, Yasuhiro; Tanoue, Kenjiro; Igarashi, Koji; Umeda, Masato; Inoue, Keizo (Thrombosis and Haemostasis, 1996)
To study the pathological functions of anti-phospholipid (anti-PL) antibodies, we have analyzed their effect on platelet function. We identified an IgG anti-PL mAb, designated PSG3, which cross-reacted specifically with glycoprotein (GP) IIIa in human platelets and inhibited platelet aggregation. PSG3 bound also to certain polyanionic substances, such as double-stranded DNA, heparan sulfate, dextran sulfate and acetylated-LDL, but not to other polyanionic substances. The binding of PSG3 to GPIIIa was completely inhibited by heparan sulfate and dextran sulfate, indicating that PSG3 recognizes a particular array of negative charges expressed on both GPIIIa and the specified polyanionic substances. Since neither neuraminidase- nor endoglycopeptidase F-treatment of GPIIIa had any significant effect on the binding of PSG3, this array must be located within the amino acid sequence of GPIIIa but not in the carbohydrate moiety. Reduction of the disulfide bonds in GPIIIa greatly reduced its reactivity, suggesting that the negative charges in the epitope are arranged in a particular conformation. PSG3 inhibited platelet aggregation induced by either ADP or collagen, it also inhibited fibrinogen binding to activated platelets in a dose-dependent fashion. PSG3, however, did not inhibit the binding of GRGDSP peptide to activated platelets. These results suggest that the PSG3 epitope on GPIIIa contains a particular array of negative charges, and possibly affects the fibrinogen binding to GPIIb/IIIa complex necessary for platelet aggregation.